THE INFLUENCE OF HUMAN RELATIONS AND WORK ENVIRONMENT ON EMPLOYEE WORK ETHIC AT PT. MALEA ENERGY TANA TORAJA DISTRICT - Pagiu, Chrismesi; Febrian, Febrian (JURNAL EKBIS, 2024)
The purpose of this research is to determine whether human relations and work environment work environment affect the work ethic of employees at PT Malea Energy Tana Toraja Regency. Data collection techniques in this research is by observation and distributing questionnaires. Analysis technique using multiple linear regression test. Partial test results show that (t test) human relation variable and work environment work environment affect the work ethic of employees at PT Malea Energy Tana Toraja Regency. Meanwhile, the results of simultaneous testing (F test) test results show that human relation variables and work environment affect the work ethic of employees at PT. Malea Energy Energy Tana Toraja Regency